Pembuatan Pupuk Organik Cair Berbahan Dasar Limbah Organik Pasar MMTC Medan - Saronom Silaban; Murniaty Simorangkir; Juniar Hutahaean; Choms Gary Ganda Tua Sibarani; Marudut Sinaga; Bajoka Nainggolan; Martua Haojahan Saragih; Kristin Wulan Liberti Vivanis Gulo; Litani Fivetrin Siregar; Fuaddinda Putri Salsabila (Cv. Utility Project Solution, 2022)
This community partnership program (PKM) activity aims to train and assist farmer group partners